Salicylic Acid-Mediated Disturbance Increases Bacterial Diversity in the Phyllosphere but Is Overcome by a Dominant Core Community - Vincent, Stacey A.; Ebertz, Andreas; Spanu, Pietro D.; Devlin, Paul F. (Frontiers in Microbiology, 2022)
Plant microbiomes and immune responses have coevolved through history, and this applies just as much to the phyllosphere microbiome and defence phytohormone signalling. When in homeostasis, the phyllosphere microbiome confers benefits to its host. However, the phyllosphere is also dynamic and subject to stochastic events that can modulate community assembly. Investigations into the impact of defence phytohormone signalling on the microbiome have so far been limited to culture-dependent studies; or focused on the rhizosphere. In this study, the impact of the foliar phytohormone salicylic acid (SA) on the structure and composition of the phyllosphere microbiome was investigated. 16S rRNA amplicons were sequenced from aerial tissues of two Arabidopsis mutants that exhibit elevated SA signalling through different mechanisms. SA signalling was shown to increase community diversity and to result in the colonisation of rare, satellite taxa in the phyllosphere. However, a stable core community remained in high abundance. Therefore, we propose that SA signalling acts as a source of intermediate disturbance in the phyllosphere. Predictive metagenomics revealed that the SA-mediated microbiome was enriched for antibiotic biosynthesis and the degradation of a diverse range of xenobiotics. Core taxa were predicted to be more motile, biofilm-forming and were enriched for traits associated with microbe-microbe communication, offering potential mechanistic explanation of their success despite SA-mediated phyllospheric disturbance.